Language and Teaching Methodology Features of CLIL in University Classrooms: A Research Synthesis - Fajardo Dack, Tammy Mercedes; Argudo, Juanita; Abad, Mónica (Colombian Applied Linguistics Journal, 2020)
Content and language integrated learning (CLIL) is a dual focus educational approach widely used in European primary, secondary and tertiary education institutions in which content subjects included in the mainstream curriculum are taught through a foreign language, usually English. This paper presents a systematic review on relevant existing literature on the application of the CLIL approach in university classrooms. A total of 22 studies were identified and chosen for further analysis; the categories emerged from the analysis itself. These studies, which focused on language and methodological features, were explored to determine the research trends in terms of location, methodology, participants, data collection instruments, focus, teaching methodology and language focus. The results of the review show a trend to examine classroom discourses and the development of pragmatic competence in CLIL classrooms. As a result of the review, the paper offers suggestions for future research on the CLIL approach in university classrooms as more tertiary education institutions around the globe are adopting English as the language of instruction.